Phase III, Randomized Study of Dual Human Epidermal Growth Factor Receptor 2 (HER2) Blockade With Lapatinib Plus Trastuzumab in Combination With an Aromatase Inhibitor in Postmenopausal Women With HER2-Positive, Hormone Receptor–Positive Metastatic Breast Cancer: Updated Results of ALTERNATIVE. Issue 1 (1st January 2021) - Johnston, Stephen R. D.; Hegg, Roberto; Im, Seock-Ah; Park, In Hae; Burdaeva, Olga; Kurteva, Galina; Press, Michael F.; Tjulandin, Sergei; Iwata, Hiroji; Simon, Sergio D.; Kenny, Sarah; Sarp, Severine; et al.
Abstract : PURPOSE: Human epidermal growth factor receptor 2 (HER2) targeting plus endocrine therapy (ET) improved clinical benefit in HER2-positive, hormone receptor (HR)–positive metastatic breast cancer (MBC) versus ET alone. Dual HER2 blockade enhances clinical benefit versus single HER2 blockade. The ALTERNATIVE study evaluated the efficacy and safety of dual HER2 blockade plus aromatase inhibitor (AI) in postmenopausal women with HER2-positive/HR-positive MBC who received prior ET and prior neo(adjuvant)/first-line trastuzumab (TRAS) plus chemotherapy. This updated article reflects minor numerical corrections in some secondary efficacy analyses that resulted from programming errors and that do not change the major conclusions of the study. METHODS: Patients were randomly assigned (1:1:1) to receive lapatinib (LAP) plus TRAS plus AI, TRAS plus AI, or LAP plus AI. Patients for whom chemotherapy was intended were excluded. The primary end point was progression-free survival (PFS; investigator assessed) with LAP plus TRAS plus AI versus TRAS plus AI. Secondary end points were PFS (comparison of other arms), overall survival (OS), overall response rate (ORR), clinical benefit rate (CBR), and safety. RESULTS: Three hundred fifty-five patients were included in this analysis: LAP plus TRAS plus AI (n = 120), TRAS plus AI (n = 117), and LAP plus AI (n = 118). Baseline characteristics were balanced. The study met its primary end point; superior PFS was observed with LAP plus TRAS plus AI versus TRAS plus AI (median PFS, 11 v 5.6 months; hazard ratio, 0.62 [95% CI, 0.45 to 0.88]; P = .0063). A consistent PFS benefit was observed in predefined subgroups. ORR, CBR, and OS also favored LAP plus TRAS plus AI. The median PFS with LAP plus AI versus TRAS plus AI was 8.3 versus 5.6 months (hazard ratio, 0.85 [95% CI, 0.62 to 1.17]; P = .3159). Common adverse events (AEs; ≥ 15%) with LAP plus TRAS plus AI, TRAS plus AI, and LAP plus AI were diarrhea (69%, 9%, and 51%, respectively), rash (36%, 2%, and 28%, respectively), nausea (22%, 9%, and 22%, respectively), and paronychia (30%, 0%, and 15%, respectively), mostly grade 1 or 2. Serious AEs were reported similarly across the 3 groups, and AEs leading to discontinuation were lower with LAP plus TRAS plus AI. CONCLUSION: Dual HER2 blockade with LAP plus TRAS plus AI showed superior PFS benefit versus TRAS plus AI in patients with HER2-positive/HR-positive MBC. This combination offers an effective and safe chemotherapy-sparing alternative treatment regimen for this patient population.